1982
DOI: 10.1002/recl.19821011101
|View full text |Cite
|
Sign up to set email alerts
|

Flash vacuum thermolysis, a versatile method in organic chemistry. Part II, fragmentation patterns in specific classes

Abstract: In Part I, Flash Vacuum Thermolysis' (FVT) was presented as a routinely available technique, with a unique preparative potential for several, often theoretically interesting, classes of organic compounds and also as an aid in mechanistic research, e.g. for describing the thermal energy surface of a species*. Here, our FVT results, obtained using specific classes of compounds, are related to selected literature data and an attempt is made to distinguish general FVT reaction patterns from the growing number of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…Wiersum confirmed this reaction under FVP conditions. 21 No yield was given, but it was mentioned that polymeric material was also formed.…”
Section: 23-triazolesmentioning
confidence: 84%
See 2 more Smart Citations
“…Wiersum confirmed this reaction under FVP conditions. 21 No yield was given, but it was mentioned that polymeric material was also formed.…”
Section: 23-triazolesmentioning
confidence: 84%
“…In his classic monograph, Hurd lists many examples of pyrolysis of organic compounds by passing vapors through red-hot tubes at atmospheric pressure . In contrast, in FVP, a sample is volatilized into a resistively heated pyrolysis tube, usually quartz, in high vacuum, usually 10 –3 –10 –5 hPa, and the products are collected in a liquid nitrogen cold trap or condensed with Ar at 10–22 K to form a matrix. , Detailed descriptions of several types of apparatus have been published, including the coupling of a FVP apparatus with matrix isolation equipment. Many examples of FVP–matrix isolation with IR, UV–vis, or electron spin resonance (ESR) spectroscopic characterization of the products will be given in this review.…”
Section: The Fvp Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyrolysis of 1-acylbenzotriazoles results in N 2 elimination and cyclization to benzoxazoles, but the yields of these compounds are low. Online mass spectrometry and low-temperature IR spectroscopy revealed that the FVP of 1-acetylbenzotriazole 8 (Scheme ) caused ring contraction to N -acetylfulvenimine 11 in addition to the formation of 2-methylbenzoxazole 13 , thus explaining why the yield of the latter is low .…”
Section: Resultsmentioning
confidence: 99%